Selective excision of the centromere chromatin complex from Saccharomyces cerevisiae (The Rockefeller University Press, 1988)
We have taken advantage of the known structural parameters associated with centromere DNA in vivo to construct a CEN fragment that can be selectively excised from the chromatin DNA with restriction endonucleases. CEN3 DNA is organized in chromatin such that a 220-250- bp region encompassing the elements of centromere homology is resistant to nuclease digestion. Restriction enzyme linkers encoding the Bam HI- recognition site were ligated to a 289 base pair DNA segment that spans the 220-250-bp protected core (Bloom et al., 1984). Replacement of this CEN3-Bam HI linker cassette into a chromosome or plasmid results in formation of a complete structural and functional centromeric unit. A centromere core complex that retains its protected chromatin conformation can be selectively excised from intact nuclei by restriction with the enzyme Bam HI. The centromeric protein-DNA complex is therefore not dependent upon the intact torsional constrains on linear chromosomes for its structural integrity. Isolation of this complex provides a novel approach to characterizing authentic centromeric proteins bound to DNA in their native state.